Targeting fibroblast growth factor (FGF)-21: a promising strategy for metabolic dysfunction-associated steatotic liver disease treatment - Cui, Xinyue; Sun, Quanhao; Wang, Haiqiang (Frontiers in Pharmacology, 2025)
Metabolic dysfunction-associated steatitic liver disease (MASLD) is the predominant chronic liver disease, with its incidence increasing year by year. It has emerged as the most rapidly increasing contributor to liver-related mortality worldwide and is becoming a principal cause of end-stage liver disorders, primarily cancer of the liver and liver transplantation, hence putting a substantial economic burden on public health. The approval of Resmetirom signifies significant advancement in the treatment of metabolic dysfunction-associated steatohepatitis (MASH); nonetheless, the heterogeneity of MASLD renders it challenging for a single medication to address the requirements of all patients. Consequently, it is essential to formulate varied therapeutic approaches for distinct pathogenic causes and phases of disease. Fibroblast growth factor 21 (FGF21), a member of the fibroblast growth factor family, plays a positive and protective role in MASLD. It attenuates hepatic steatosis and lipotoxicity, ameliorates insulin resistance (IR), reduces oxidative stress, endoplasmic reticulum (ER) stress, and inflammation, as well as possesses anti-fibrotic effects. As a result, FGF21 has the potential to treat MASLD. In this review, we will address the possible mechanisms of FGF21 therapy for MASLD to facilitate the development of clinical therapies targeting FGF21 for MASLD.